(untitled) (Journal of the Management Sciences, 2025)
The performance of the stock market plays a crucial role in mobilizing resources and fostering economic growth in emerging economies such as Nigeria. However, despite its potential, concerns persist regarding the efficiency of capital utilization and the quality of governance in driving sustainable development. This study investigates Stock Market Development and Sustainable Economic Growth in Nigeria: An Empirical Analysis between 1990 and 2022. Using annual time series data from the World Development Indicators and Worldwide Governance Indicators, the study applies the Autoregressive Distributed Lag (ARDL) technique to capture both short-run and long-run dynamics. The results show that gross fixed capital formation exerts a negative and significant effect on growth, indicating inefficiencies in capital investment. In contrast, stock market capitalization has a positive and significant influence, underscoring the stock market’s role as a driver of economic expansion. Governance quality, measured by the rule of law, is negatively associated with growth, highlighting institutional weaknesses that hinder Nigeria’s development trajectory. The findings suggest that improving stock market depth and efficiency can contribute to long-term growth, while weak governance remains a major constraint. It is therefore recommended that policymakers strengthen institutional frameworks, enhance the rule of law, promote investor confidence, and implement reforms that deepen capital market activities. Such measures will foster inclusive and sustainable economic growth in Nigeria.